Geology and structure of the Pokhara-Piuthan area, central Nepal (Journal of Nepal Geological Society, 1982)
The geological mapping of the present area revealed that the area is a transitional area between central and western Nepal. The Kali Gandaki - Bari Gad fault which runs obliquely to the general Homalayan trend separates the present area lithostrato- tectonically into the northeast and soutewest units. Both units are in contrast each other in many respects. The northeast unit comprises the Tibetan Tethys, Himalayan gneiss, Main Central Thrust, Baglung and Bihadi zones. The last two are composed of the Midland meta- sediment Group of Riphean to Eocambrian age and autochthonous in character. The Himalayan gneisses are thrust over the Midland meta-sediments by the Main Central Thrust zone forming a klippe in the southwest unit. On the other hand the southwest unit consists mainly of slightly metamorphosed sediments probably of Paleozoic age which are folded and faulted as compared to those of the northeast unit. The metamorphic grade of the latter is obviously higher than the foemer.The present area, particularly the Kali Gandaki. Bari Gad fault is of exteme significance in considering the tectonic flame of the Nepal Himalayas.